Pengaruh Pelatihan, Kecerdasan Emosional, dan Disiplin Kerja terhadap Produktivitas Kerja Karyawan pada Sinar Steak House - Hendy Hendy; Victor Victor; Calvin Yudha (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to describe the effect of training, emotional intelligence and work discipline on employee work productivity at Sinar Steak House. This study was conducted for 6 (six) months, starting from November 2024 to April 2025. The respondents of this study were 32 (thirty-two) Sinar Steak House employees. The instrument used was a questionnaire to collect data from training variables, emotional intelligence variables and work discipline variables. The data analysis techniques used were validity testing, reliability testing, descriptive analysis, normality testing, multiple linear regression analysis, partial hypothesis testing or t-test and calculation of the coefficient of determination. Determination of the results of descriptive analysis for training variables, emotional intelligence variables and work discipline are in the very good category. Based on partial analysis, training has a positive and significant effect on employee work productivity at Sinar Steak. For the emotional intelligence variable, it has a partial positive and significant effect on employee work productivity at Sinar Steak. For the work discipline variable, it has a partial positive and significant effect on employee work productivity at Sinar Steak. Based on the simultaneous analysis of training, emotional intelligence and work discipline, it has a positive and significant effect on employee work productivity at Sinar Steak.